“Røret er koldt i hånden” - Telefonen i dansk litteratur og kultur 1876-2014 - Johansen, Martin Gerster; Høgh, Søren Langager (Passage - Tidsskrift for litteratur og kritik, 2014)
Martin Gerster Johansen & Søren Langager Høgh: “‘Røret er koldt i hånden’: The Telephone in Danish Literature and Culture 1876-2014” Through a double perspective of literature and cultural history, this article describes the telephone’s historical status in a Danish context. While phone technology in the cultural-historical perspective has usually been received with either jubilation or fear, the article shows how the phone in more recent Danish literature appears in a more nuanced and calm way. Specialized knowledge of telephones and their history is coupled with close readings of a range of Danish works including the authors Harald Kidde, Emil Bønnelycke, Helle Helle, Lone Hørslev and Klaus Høeck. The hypothesis is that literature holds a large and pristine field of phone knowledge and the aim of the article is to expose this knowledge.